2020
DOI: 10.3390/ijms21207767
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Changes in a Pediatric Series Treated with Off-Label JAK Inhibitors

Abstract: Off-label use of medications is still a common practice in pediatric rheumatology. JAK inhibitors are authorized in adults in the treatment of rheumatoid arthritis, psoriatic arthritis and ulcerative colitis. Although their use is not authorized yet in children, JAK inhibitors, based on their mechanism of action and on clinical experiences in small series, have been suggested to be useful in the treatment of pediatric interferon-mediated inflammation. Accordingly, an increased interferon score may help to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
0
19
0
2
Order By: Relevance
“…A recent case report of three cSLE patients allergic to rituximab demonstrated that ofatumumab, a fully humanized anti-CD20 monoclonal antibody, was a safe, well tolerated, and effective alternative for B-cell depletion [ 156 ]. Another report suggested Janus kinase (JAK) inhibitors as an alternative treatment for pediatric patients with severe IFN-mediated inflammatory disorders, including cSLE patients, reducing progressively inflammatory markers, IFN score, and inducing upregulation of the DNA repair pathway [ 157 ].…”
Section: Management Data and Drugs For Cslementioning
confidence: 99%
“…A recent case report of three cSLE patients allergic to rituximab demonstrated that ofatumumab, a fully humanized anti-CD20 monoclonal antibody, was a safe, well tolerated, and effective alternative for B-cell depletion [ 156 ]. Another report suggested Janus kinase (JAK) inhibitors as an alternative treatment for pediatric patients with severe IFN-mediated inflammatory disorders, including cSLE patients, reducing progressively inflammatory markers, IFN score, and inducing upregulation of the DNA repair pathway [ 157 ].…”
Section: Management Data and Drugs For Cslementioning
confidence: 99%
“…Of note, one PRAAS patient discontinued the treatment due to acute renal injury related to BK virus infection and subsequently died after a relapse of his disease and a respiratory tract infection. Nevertheless, these very encouraging results in PRAAS were further confirmed by two single patient cases treated with another JAKinib (tofacitinib) (91,92).…”
Section: Praasmentioning
confidence: 83%
“…Studies from four different teams demonstrated that mutations in COPA led to STING-mediated IFN signaling and defined a role for wild-type COPA in STING retrieval from the Golgi back to the ER to prevent chronic immune activation (85)(86)(87)(88). Considering these data, a few COPA patients (five in total) have been treated with JAKinib (85,(89)(90)(91) and follow-up on treatment has been reported for 3 (89)(90)(91). Complete or partial remission has been achieved for arthritis in two patients (89,91) while a major improvement was observed in a COPA patient with a severe diffuse alveolar hemorrhage (90).…”
Section: Copamentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, four molecules received market authorization in humans: tofacitinib (acting on JAK1, JAK2, and JAK3), baricitinib, upadacitinib, and ruxolitinib (JAK1 and JAK2). These drugs have been widely used for clinical trials or as off-label prescriptions, due to their wide spectrum of actions: the effect on JAK1 and JAK2 provides the inhibition of type I and II IFNs and IL-6 signalings, and the blockade of JAK3 (particularly exerted by tofacitinib) significantly reduces the activity of other cytokines and the lymphocyte activation (IL-2, IL-4, IL-7, IL-9, IL-15, and IL-21) [ 45 ].…”
Section: From Monogenic To Multifactorial: Interferon-related Brain Disordersmentioning
confidence: 99%